Exogenous Liquidity Supply in Presence of Repudiation Risk and Private Asset Recovery - GURDGIEV, CONSTANTIN (My University, 2003)
Current paper proposes an extension of the seminal model by Holmstrom Tirole (1997) of the exogenous liquidity supply in presence of moral hazard to the case that includes private asset recovery under the limited liability of the entrepreneur. In our model partial private recovery applies to the financial assets that are considered to be sunk by the investors. In this context, a distressed firm seeking second round financing for its investment project is able, within a limited range of shocks, to increase its private payoff in case of the project default. As the result, unable to use these funds to raise additional liquidity, the distressed firms faces a reduced range of acceptable shock values relative to Holmstrom Tirole set up. At the same time, domestic securities markets, even in absence of aggregate uncertainty, are shown to hold insufficient liquidity. As the result, distressed firms individually are unable to counter the shocks by holding claims against other firms even in case of the financial intermediation.
PUBLISHED
Keywords: Economics; Investment; Asymmetric Information; Repudiation Risk; Private Information; Holmstrom Tirole model